Islamic bioethics of pain medication: an effective response to mercy argument - Malik, Mohammad Manzoor (Bangladesh Bioethics Society (BBS), 2012)
Pain medication is one of the responses to the mercy argument that utilitarian ethicists use for justifying active euthanasia on the grounds of prevention of cruelty and appeal to beneficence. The researcher reinforces the significance of pain medication in meeting this challenge and considers it the most preferred response among various other responses. It is because of its realism and effectiveness. In exploring the mechanism and considerations related to pain medication, the researcher briefly touches the Catholic ethical position on the issue, a position that cannot be ignored in the development of contemporary bioethics. The researcher particularly deliberates on the contemporary Islamic discourse on the issue; by furthering the debate in line with the Islamic legal maxims and general guidance from the primary sources of Islamic law and ethics. The resolution on the issue is sought by synthesizing the views and legal maxims (al-Qawaid al-Fiqhiyyah) on the issue, which in conclusion provide justification for pain medication by considerably regarding pain as “necessity” and “pressing need”. However, such resolution allows pain medication to the limit and proportion that removes the pain and prohibits overdosing the patient with medication that may directly cause the death.